EKSISTENSI FILSAFAT EKONOMI ISLAM TERHADAP PENGUATAN HALAL SUPPLY CHAIN DI INDONESIA - Miftahul Jannah; Syukri Iska; Azifah Hidayati; Siska Putri; Fandi Ahmad Marlion (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
Halal supply chain practices in Indonesia still face various challenges that must be strengthened for their sustainability. One such challenge is the application and linking of principles in Islamic economic philosophy with the principles of the Halal Supply Chain. The purpose of this study is to analyze the existence of Islamic economic philosophy principles in strengthening the halal supply chain, as well as to observe the implementation of the relationship between Islamic economic philosophy principles and halal supply chain principles. This study uses a descriptive qualitative approach with a literature study method with the aim of describing the social phenomena that occur in in-depth detail. The results show that the principles of Islamic economic philosophy such as tauhid, justice, amanah, maslahah, and mizan are relevant and applicable normative foundations in strengthening the halal supply chain (HSC). These values ​​are then realized operationally through the principles of sharia compliance, halal integrity, traceability, transparency, sharia risk management, and professionalism in logistics management. The conclusion of this study is that the existence of Islamic economic philosophy significantly contributes to strengthening the concept, mechanism, and implementation of the halal supply chain (HSC) in Indonesia.